Baby Oil as Evidence-Based Nursing for Uremic Pruritus in Chronic Kidney Disease Patients - Handika, Bintang Viga; Kristinawati, Beti; Kristini, Puji (Universitas Muhammadiyah Semarang, 2023)
One of the effects that occur in chronic kidney failure can cause metabolic waste not to be eliminated by the kidneys and accumulate on the skin, which causes itching or commonly known as pruritus. Treatments to reduce pruritus can use emollient oil or baby oil that can keep the skin moist. This implementation aims to determine the effectiveness of baby oil in chronic kidney disease (CKD) patients with uremic pruritus. This implementation is based on the results of previous research using experimental, pretest and posttest design. The population was CKD patients undergoing hemodialysis (HD) with uremic pruritus. This sample determination is based on the inclusion and exclusion criteria that have been built and the sample size was 22 HD patiens. Results showed that pruritus score was decreased up to 2,72. It shows the effectiveness of baby oil on uremic pruritus in CKD patients undergoing HD treatment.